A Toolkit for High Resolution Imaging of Cell Division and Phytohormone Signaling in Legume Roots and Root Nodules - Nadzieja, Marcin; Stougaard, Jens; Reid, Dugald (Frontiers in Plant Science, 2019)
Legume plants benefit from a nitrogen-fixing symbiosis in association with rhizobia hosted in specialized root nodules. Formation of root nodules is initiated by de novo organogenesis and coordinated infection of these developing lateral root organs by rhizobia. Both bacterial infection and nodule organogenesis involve cell cycle activation and regulation by auxin and cytokinin is tightly integrated in the process. To characterise the hormone dynamics and cell division patterns with cellular resolution during nodulation, sensitive and specific sensors suited for imaging of multicellular tissues are required. Here we report a modular toolkit, optimized in the model legume Lotus japonicus, for use in legume roots and root nodules. This toolkit includes synthetic transcriptional reporters for auxin and cytokinin, auxin accumulation sensors and cell cycle progression markers optimized for fluorescent and bright field microscopy. The developed vectors allow for efficient one-step assembly of multiple units using the GoldenGate cloning system. Applied together with a fluorescence-compatible clearing approach, these reporters improve imaging depth and facilitate fluorescence examination in legume roots. Given the prominent auxin signal associated with nodule development, we also tested whether a classical root gravitropism assay could alter the timing and location of auxin accumulation and nodule emergence. We show that alteration of auxin distribution in roots allows for preferential nodule emergence at the outer side of the bend corresponding to a region of high auxin signalling capacity. The presented tools and procedures open new possibilities for comparative mutant studies and for developing a more comprehensive understanding of legume-rhizobia interactions.